Experimental investigation on modes of spray formation, droplet size and size distribution in a spinning disc atomizer - Chen, Jian; Hu, Wei; Dong, Xiaoya; Lin, Jinlong; Gao, Zhouming; Qiu, Baijing (Frontiers in Plant Science, 2024)
The spinning disc atomizer is extensively utilized in agricultural spraying, with optimized operating conditions significantly enhancing atomization performance. In this paper, the atomization characteristics of a spinning disc were studied using photographs taken by a high-speed camera. Ethanol-water solutions were used at various flow rates and the disc speed was varied in a wide range. The influence of disc speed, flow rate, and surface tension on modes of spray formation, droplet size, and size distribution were investigated. The correlations for Reynolds number (Re), Stability number (St), and dimensionless droplet size (d * ) were proposed in a wide range of operational conditions. The Rosin-Rammler (RR) and modified Rosin-Rammler (MRR) distributions appropriately represented the droplet size distribution. It was found that the increase in flow rate resulted in modes of spray formation translation under the same disc speed and ethanol-water solution. The predicted droplet sizes showed good agreement with the experiment values. Most of the predicted droplet sizes were within the band of ±15% of the experiment values. The droplet size decreased with increasing Re or St, but was hardly affected by q. Besides, the droplet size decreased with increasing disc speed and decreasing surface tension. The RR and MRR distribution matched with the calculated cumulative volume fraction from the experimental data reasonably well for the entire range. It was recommended to appropriately elevate Re during the spinning disc atomization process to narrow the range of droplet sizes and enhance uniformity.